Irisin Role in Chondrocyte 3D Culture Differentiation and Its Possible Applications - Francesca Posa; Roberta Zerlotin; Anastasia Ariano; Michele Di Cosola; Graziana Colaianni; Aldo Di Fazio; Silvia Colucci; Maria Grano; Giorgio Mori (MDPI AG, 2023)
Irisin is a recently discovered cytokine, better known as an exercise-induced myokine, produced primarily in skeletal muscle tissue as a response to exercise. Although the skeleton was initially identified as the main target of Irisin, its action is also proving effective in many other tissues. Physical activity determines a series of beneficial effects on health, including the possibility of counteracting the damage that is caused by arthritis to the cartilage of people suffering from osteoarthritis. Nevertheless, up to now, the studies that have taken into consideration the possible involvement of Irisin on the well-being of cartilage tissue are particularly limited. In this study, we postulated that the protective effect of physical activity on cartilage tissue may depend on the paracrine action of Irisin secreted during exercise; therefore, we analyzed the effects of Irisin, in vitro, on chondrogenic differentiation. To achieve this goal, three-dimensional cultures of commercially available human articular chondrocytes (HACs) were treated with the molecule under study. Our results revealed new crosstalk mechanisms between muscle and cartilage tissue. Furthermore, the confirmation of Irisin ability to induce chondrogenic differentiation could favor the development of exercise-mimetic drugs, with application relevance for patients who cannot perform physical activity.